Ethnobotany of medicinal plants used in Eastern Mallorca (Balearic Islands, Mediterranean Sea) - Carrió, Esperança; Vallès, Joan (Journal of Ethnopharmacology, 2012)
Ethnopharmacological relevance: This paper represents the ﬁrst large-scale ethnobotanical study in the island of Mallorca, and provides signiﬁcant information on pharmaceutical plant uses, built up from interviews with native people from this touristic hotspot, demonstrating its ethnopharmacological importance. Aim of the study: To collect, analyse and evaluate the ethnobotanical knowledge concerning medicinal plants in a north-eastern Mallorcan area (municipalities of Artà, Capdepera and Son Servera; 298 km2 , 31,764 inhabitants). Materials and methods:We performed semi-structured interviews with 42 informants (mean age 77; 40% women, 60% men), identiﬁed the plant taxa reported and analysed the results, comparing them with those found in the current Mallorcan ethnobotanical information and in other territories. Results: The informants reported data on 121 human medicinal plants representing 64 botanical families. Around 45 medicinal uses reported, concerning 37 species, have not or have very rarely been cited as medicinal. An index of medicinal importance is proposed. Conclusions: All efforts addressed to compiling ethnobotanical information in industrialised or touristised areas such as Eastern Mallorca are still valuable. New possibilities can be explored to give practical value to Mallorcan ethnobotanical data in the frame of considering traditional plant knowledge as part of the islanders’ lifestyle and healthy habits.
Keywords: catalan-speaking territories; Mallorcan ethnopharmacopoeia; Mediterranean ethnobotany; Plant uses; traditional plant knowledge

Plant ethnoveterinary practices in two pyrenean territories of catalonia (iberian peninsula) and in two areas of the balearic islands and comparison with ethnobotanical uses in human medicine. - Carrió, Esperança; Rigat, Montse; Garnatje, Teresa; Mayans, Marina; Parada, Montse; Vallès, Joan (Evidence-based complementary and alternative medicine : eCAM, 2012)
This paper presents the results of an ethnobotanical study centred in veterinarian uses in two Catalan Pyrenean regions (Alt Empordà -AE- and High River Ter Valley -AT-, Iberian peninsula) and two Balearic Islands areas (Formentera -FO- and northeastern Mallorca -MA-). In the areas studied, 97 plant species have been claimed to be useful for veterinary purposes. A total of 306 veterinary use reports have been gathered and analysed. The ten most reported plants are Tanacetum parthenium (24 use reports), Parietaria officinalis (15), Ranunculus parnassifolius (14), Meum athamanticum (13), Olea europaea (13), Quercus ilex (12), Ruta chalepensis (12), Sambucus nigra (10) and Thymus vulgaris (10). According to comprehensive reviews, a high number of novelties for plant ethnoveterinary are contributed: 34 species and one subspecies, 11 genera, and three families have not been reported in previous works in this field, and 21 species had only been mentioned once. Several ethnoveterinary uses are coincidental with those in human medicine. Although ethnoveterinary practices are less relevant than in the past in the territories considered, as in all industrialised countries, the knowledge on plant properties and applications is still rich and constitutes a large pool of evidence for phytotherapy, both in domestic animals and humans.
The following values have no corresponding Zotero field: accession-num: 22829861
Keywords: Ethnobotany; medicinal plants (PG); Veterinary medicine